Prevalence of hepatitis B virus infection in a municipality of Acre State, Western Amazonia, Brazil - Silva, Rita do Socorro Uchôa da (2019)
OBJECTIVE: To estimate the prevalence of hepatitis B virus (HBV) in individuals living in Porto Acre municipality, Acre State, Western Brazilian Amazon. MATERIALS AND METHODS: Cross-sectional study carried out with residents of Porto Acre who had attended the basic health units in 2012 were invited to answer a standardized questionnaire and to donate venous blood. As screening, immunochromatographic rapid test (IRT) for hepatitis B (HBsAg) was used, and from whom that was reagent to the IRT, serological tests (HBsAg and total anti-HBc) were performed. The HBeAg, anti-HBe and total anti-HD markers were used exclusively in the samples whose HBsAg remained serologically reagent. RESULTS: It was included 646 individuals (4.7% of the population), 57.6% of the female gender. Seventeen individuals (2.6%) were reagent to the IRT for HBsAg and of which in 82.3% (14/17) presented serological confirmation. Total anti-HBc was reactive in 31.9% (206/646) of the subjects, of which 2.2% (14/646) had current HBV and 29.7% (192/646) only evidence of previous infection. Of the 184 (28.5%) children and adolescents included in this study, 9.2% (17/184) had prior contact with HBV. The abusive alcohol intake is correlated to HBsAg and total anti-HBc reactivity, whereas older age, male gender, previous surgeries, and the presence of tattoos were related exclusively to total anti-HBc higher reactivity. CONCLUSION: HBsAg seroprevalence was 2.2% and total anti-HBc approximately 32.0%. There was detection of total anti-HBc in 9.2% of the children and adolescents included in the study, evidencing early contact with HBV in this population.